Sex Differences in Long-Term Cause-Specific Mortality After Percutaneous Coronary Intervention: Temporal Trends and Mechanisms. (March 2018) - Raphael, Claire E.; Singh, Mandeep; Bell, Malcolm; Crusan, Daniel; Lennon, Ryan J.; Lerman, Amir; Prasad, Abhiram; Rihal, Charanjit S.; Gersh, Bernard J.; Gulati, Rajiv
Abstract : Background—: Women have higher rates of all-cause mortality after percutaneous coronary intervention. Whether this is because of greater age and comorbidity burden or a sex-specific factor remains unclear. Methods and Results—: We retrospectively assessed cause-specific long-term mortality after index percutaneous coronary intervention over 3 time periods (1991–1997, 1998–2005, and 2006–2012). Cause of death was determined using telephone interviews, medical records, and death certificates. We performed competing risks analyses of cause-specific mortality. A total of 6847 women and 16 280 men survived index percutaneous coronary intervention hospitalization 1991 to 2012. Women were older (mean±SD: 69.4±12 versus 64.8±11.7 years; P <0.001) with more comorbidities (mean±SD: Charlson index 2.1±2.1 versus 1.9±2.1; P <0.001). Across the 3 time periods, both sexes exhibited a decline in cardiac deaths at 5 years (26% relative decrease in women, 17% in men, trend P <0.001 for each). Although women had higher all-cause mortality compared with men in all eras, the excess mortality was because of noncardiac deaths. In the contemporary era, only a minority of deaths were cardiac (33.8% in women, 38.0% in men). After adjustment, there was no evidence for a sex-specific excess of risk for cardiac or noncardiac mortality. The commonest causes of death were chronic diseases and heart failure in women (5-year cumulative mortality, 5.4% and 3.9%) but cancer and myocardial infarction/sudden death in men (5.4% and 4.3%). Conclusions—: The higher mortality after percutaneous coronary intervention in women is because of death from noncardiac causes. This is accounted for by baseline age and comorbidities rather than an additional sex-specific factor. These findings have implications for sex-specific clinical care and trial design.